The Use of Silica Extracted from Kaolin as Catalyst Support for Esterification of 4-Hydroxybenzoic Acid with Sucrose - Iman Abdullah; Widayanti Wibowo; Soleh Kosela; Yuni Krisyuningsih Krisnandi (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
SiO2 was extracted from kaolin using concentrated HCl and HNO3 mixture and used as solid support for both Bronsted (HClO4 and H2SO4) and Lewis Acid (AlCl3 and ZnCl2). Before extraction, kaolin was calcined at 800°C for eight hours to form metastable kaolin. After the extraction procedure, silica was recovered in 51.6% yield. Silica and the resulting solid acids were then characterized using XRD, XRF, and FTIR. XRD pattern shows that silica synthesized from kaolin is in the mixture of amorphous and α-quartz silica. Immobilization of acids alters its structure becomes more crystalline. XRF analysis shows that the loading of AlCl3 and ZnCl2 was 9.5 and 24.8%, respectively. The acid catalysts were then used in the esterification reaction of 4-hydroxybenzoic acid with sucrose. The reactions were conducted in dimethyl sulfoxide (DMSO) solvent by varying reaction time and reaction temperature. The highest conversion of starting materials and selectivity towards ester was obtained over the AlCl3/SiO2 catalyst. DPPH radical scavenging test shows that the ester exhibits good antioxidant activity.